The role of plant volatiles and oviposition experience in the foraging behaviour of Diadegma semiclausum (Hym., Ichneumonidae) - LI Xin; LIU Shu-sheng (浙江大学学报. 农业与生命科学版)
The role of volatiles from cabbage plants with different treatments and oviposition experience in the foraging behaviour of Diadegma semiclausum was studied. Compared to volatiles from intact plants, those from plants that were mechanically damaged, previously host-damaged or being fed by host larvae were more attractive to D. semiclausum, and the volatiles from the plants being fed by host larvae were the most attractive. The results demonstrated that the herbivore-induced plant volatiles played an important role in inducing host searching behaviour by the parasitoid, and volatiles from the host larvae also played some role. The retention times of females on the previously host-damaged plants and the plants being fed by host larvae were longer than those on the mechanically damaged plants or the intact plants. An oviposition experience prior to the bioassay significantly imporved the efficiency of host searching by the parasitoid.